2022
DOI: 10.2196/37342
|View full text |Cite
|
Sign up to set email alerts
|

Guided Internet-Delivered Treatment for Depression: Scoping Review

Abstract: Background Studies on guided internet-delivered treatment have demonstrated promising results for patients with depressive disorder. Objective The aim of this study was to provide an overview of this research area and identify potential gaps in the research. Methods In this scoping review, web-based databases were used to identify research papers published between 2010 and 2022 where guided internet-delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 184 publications
2
6
0
Order By: Relevance
“…Future research in real-world clinical settings is warranted. Third, although the large proportion of White women in the sample is consistent with past work and higher MDD prevalence and rate of treatment seeking in women [ 10 ], greater representation of patients with other racial and gender identities would strengthen our conclusions and ongoing treatment improvements. Fourth, we had adequate power to detect moderate to large treatment effects; a larger replication is needed to explore moderators and mediators, which are important for tiered care models.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Future research in real-world clinical settings is warranted. Third, although the large proportion of White women in the sample is consistent with past work and higher MDD prevalence and rate of treatment seeking in women [ 10 ], greater representation of patients with other racial and gender identities would strengthen our conclusions and ongoing treatment improvements. Fourth, we had adequate power to detect moderate to large treatment effects; a larger replication is needed to explore moderators and mediators, which are important for tiered care models.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings add to an emerging literature demonstrating the potential of guided smartphone-based CBT to mitigate these challenges. However, although numerous seemingly efficacious therapist-supported digital treatments have been created for depression [ 10 ], few are available outside of research settings or integrated into a health care system [ 25 ]. Created in collaboration with an industry partner to accelerate the dissemination pipeline and allow for ongoing technical maintenance and improvements, Mindset for Depression is commercially available and poised to be truly scalable and successful in real clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing and tailoring transdiagnostic digital interventions would benefit greatly from identifying individuals more likely to drop out and the exact reasons for their dropout. Differing expectations, improvement or worsening of health, preference for face-to-face CBT, negative perceptions about iCBT, low motivation, lack of time, internet delivery problems, and unexpected personal circumstances were reported as reasons for dropout in general populations, while the last three have also been reported in college students ( Børtveit et al, 2022 ; Kaltenthaler et al, 2008 ; Marks et al, 2003 ; Melville et al, 2010 ; Noone and Hogan, 2018 ; Rost et al, 2017 ; Schneider et al, 2014 ; Treanor et al, 2021 ; Waller and Gilbody, 2009 ). However, reasons for intervention dropout have been severely under-investigated in college students whose digital literacy may be higher and who may differ in lifestyle from general adult populations and thus in reasons for dropout ( Abdulai et al, 2021 ; Ferrari et al, 2022 ; Moreno-Gómez et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated their usability, feasibility [ 16 - 18 ], and effectiveness in reducing depressive symptoms [ 19 - 24 ]. However, treatment dropout is often reported, both in unguided and guided internet-delivered interventions [ 25 , 26 ]. Dropout is often preceded by missed sessions or ending without completing the treatment components [ 27 ].…”
Section: Introductionmentioning
confidence: 99%